Multi-feature driven carbon emission time series coupling model for laser welding system. (October 2022) - Ge, Weiwei; Cao, Huajun; Li, Hongcheng; Zhang, Chaoyong; Li, Chengchao; Wen, Xuanhao
Abstract: Laser welding has been widely applied in the automobile manufacturing industry. However, laser welding is a carbon-emission-intensity process with complex dynamic characteristics of carbon emission, which poses serious environmental burdens. Besides, the multi-source of the carbon emission, the multi-state of the devices operation, the multi-feature of the welding component， and the time series coupling raise the dynamics and complexity of carbon emission modeling for the laser welding system. To this end, this study focuses on the multi-feature driven carbon emission time series coupling model to reveal the carbon emission characteristics and calculate the carbon emission of the laser welding system. The carbon emission boundary of the laser welding system was defined for mapping the relationship between welding features, welding methods, and influence factors. Then, the carbon emission dynamic characteristics of each device were mathematically carried out by considering various sub-device operating states and the carbon emission sources. Furthermore, the time series coupling mechanism of the carbon emission sources driven by multiple features was studied in accordance with the welding task flow, and a multi-feature driven carbon emissions model was developed based on hybrid Petri net for simulating the dynamic characteristics of carbon emission. Finally, the welding experiment of 6061 aluminum alloy and the aluminum alloy body-in-white welding unit were investigated, and the results showed the feasibility and reliability of the model. This study lays a foundation for further welding parameters and welding features sequence optimization, and presents theoretical guidance for the low-carbon design of laser welding systems. Highlights: Carbon emission dynamic characteristics of each device in the laser welding system are revealed. Time series coupling mechanism of the carbon emission sources driven by multiple features is studied. Multi-feature driven carbon emission time series coupling model is established. This research presents theoretical guidance for the low-carbon design of laser welding systems.